Identification, characterization and expression analysis of wheat RSH family genes under abiotic stress - Wang, Mengru; Hong, Wei; Wang, Youning; Han, Xiaowen; Chen, Wang; Wang, Shuping; Zhang, Yingxin; Wang, Wenli (Frontiers in Plant Science, 2023)
Guanosine pentaphosphate and guanosine tetraphosphate are collectively called (p)ppGpp (Guanosine tetraphosphate and pentaphosphate). (p)ppGpp content in plants is affected by conditions such as light, salt, pH, UV light, and environmental phytohormones. The synthesis and hydrolysis of (p)ppGpp in plants is accomplished by a class of proteins called RSH (RelA/SpoT homologs). To date, a systematic and comprehensive genome-wide analysis of the RSH gene family in wheat and its closely related species has not been conducted. In this study, 15, 14, 12, and 8 members of RSH were identified in wheat (Triticum aestivum), Triticum dicoccoides, Triticum urartu and Aegilops tauschii respectively. Based on the conserved structural domains of the RSH genes, the TaRSHs have been categorized into TaRSH and TaCRSH. The gene duplications in the TaRSH gene family were all identified as segmental duplications indicating that the TaRSH family plays a significant role in expansion and that segmental duplications maintain a degree of genetic stability. Through the analysis of transcriptome data and RT-qPCR experiments, it was observed that the expression levels of TaRSHs were upregulated in response to abiotic stress. This upregulation suggests that TaRSHs play a crucial role in enhancing the resilience of wheat to adverse environmental conditions during its growth and development. Their increased expression likely contributes to the acquisition of stress tolerance mechanisms in wheat. Especially under NaCl stress, the expression levels increased most significantly.The more detailed systematic analysis provided in this article will help us understand the role of TaRSHs and provide a reference for further research on its molecular biological functions in wheat.